PERANCANGAN SISTEM PERINGATAN DINI MENGUNAKAN FRAMEWORK TOGAF - Sintaria Br Sembiring (TeIKa, 2017)
The geographical position of Indonesia led to Indonesia is a country with a very high incidence of disasters. Besides causing material damage, the disaster also caused fatalities. Therefore, the disaster must be handle properly to minimize the risk posed towards constitutions. However in fact, the lack of data and information, and inaccuracies lead to a slow decision-making process. This research aims to make the planning of disaster management information system architecture using the TOGAF Framework with a case study of Regional Disaster Management Agency of West Java. Information system architecture to development in this study is a tool that can used by BPBDs for developing and managing information systems for disaster management. This research resulted in the information system architecture modeled with business architecture, application architecture, data architecture, technology architecture, evaluation gap, and migration plans. Enterprise architecture modeling made to produce blueprint development of information systems for disaster management.